The contribution of al-Māturīdī: reason, tolerance, and integration - Rahman, Shukran Abdul; Muhammad Yusoff, Muhammad Fawwaz (HADI, 2025)
Al-Māturīdī, one of the greatest theologians of Sunni Islam and a native son of Samarkand, was celebrated as a paragon of rational faith, epistemic humility, and doctrinal balance. One of the most distinctive features of al-Māturīdī's tradition is its emphasis on contextual understanding, that Islamic teachings must be understood and practiced in ways that are meaningful and relevant to the cultures and societies in which Muslims live.